1984
DOI: 10.1038/307708a0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of altered chromatin structures by simian virus 40 enhancer and promoter elements

Abstract: Two simian virus 40 transcriptional promoter elements, the 72-base pair (bp) repeat and the 21-bp repeat region, induce chromatin structures of increased DNase I sensitivity when transposed elsewhere in the viral genome. The induction of a sufficiently long stretch of DNase I-sensitive chromatin leads to the appearance of a visible nucleosome-free region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
88
3

Year Published

1984
1984
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(94 citation statements)
references
References 39 publications
3
88
3
Order By: Relevance
“…Determinants found in a restricted region of the SV40 genome are sufficient to generate an endonuclease-sensitive region in SV40 chromatin (10,11,17,30). Starting with a viable double-origin mutant, in(Or)1411 (constructed by T. Shenk [24]), we have isolated a collection of deletion mutations which remove segments of DNA at various locations throughout the nuclease-sensitive region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determinants found in a restricted region of the SV40 genome are sufficient to generate an endonuclease-sensitive region in SV40 chromatin (10,11,17,30). Starting with a viable double-origin mutant, in(Or)1411 (constructed by T. Shenk [24]), we have isolated a collection of deletion mutations which remove segments of DNA at various locations throughout the nuclease-sensitive region.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic elements can act independently within the region of nuclease sensitivity to generate specific hypersensitive sites. A DNA segment containing the 72-bp tandem repeats (and the transcriptional enhancer) creates a DNase I-sensitive site over itself when placed at various positions around the viral genome (10,17). A segment containing the 21-bp tandem repeats forms a DNase I-sensitive site over adjacent sequences even when separated from the 72-bp repeats (10,17 We have investigated the genetic elements responsible for the chromatin structure in this region by analyzing a number of additional mutants.…”
mentioning
confidence: 99%
“…This was proposed to occur by a nucleosome exclusion mechanism wherein NFI binding simply prevented the binding of nucleosomes over the adjacent elements required for SV40 replication. In its natural context, the SV40 origin is indeed preferentially cleared of nucleosomes and is adjacent to sites with dual roles in transcription and replication (21,27). This model also implies that many transcription factors might have the potential to affect replication when bound near origins.…”
mentioning
confidence: 95%
“…We propose that the formation of the LCR HSs is a multistep process and that the first step is the binding of non-erythroid factors such as Sp1 to the core-forming element. Supporting data for this function of Sp1 come from in vitro studies from Workman and co-workers (58) showing that Sp1 is able to bind to nucleosome-associated DNA and from Jongstra et al (59) and Widlak et al (60), who demonstrated that Sp1 participates in the formation of the nuclease HSs of the SV40 early gene promoter and human immunodeficiency virus, type I LTR. Data from Pondel et al (61) indicate that Sp1 is critical for the chromatin-dependent expression of the human ␣-globin gene, and work from Marin et al (62) shows that embryonic globin genes were expressed at reduced levels in Sp1 homozygous knockout mice.…”
Section: ␤-Globin Lcr Hs Core Formationmentioning
confidence: 99%